2019
DOI: 10.1001/jamanetworkopen.2019.2589
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Use of Sipuleucel-T to Treat Patients With Advanced Prostate Cancer

Abstract: Key Points Question How is sipuleucel-T being used to treat patients with advanced prostate cancer, and what are the factors driving its use? Findings In this cohort study of 7272 patients treated for metastatic castration-resistant prostate cancer, 730 (10.0%) received sipuleucel-T. Factors such as a patient’s ethnicity, geographic region, income, and the specialty of the physician managing their treatment were associated with use of sipuleucel-T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Although the cause of prostate cancer is not yet fully understood, many studies have suggested that several risk factors are associated with the development of prostate cancer, including environmental factors, family history, age, and lifestyle [5,6]. At present, various treatments are accessible for patients with PCa using Western medicine, including radical prostatectomy (RP, removal of the prostate), radiotherapy (use of high-energy X-rays to kill cancer cells), chemotherapy (use of chemicals to kill cancer cells), androgen deprivation therapy, and immune therapy [7,8,9,10,11,12,13]. However, these therapies are costly and often cause a series of adverse side effects, such as decreased libido, erectile dysfunction, hot flashes, night sweats, castration syndrome, including such symptoms as anemia, metabolic abnormalities, and radioactive inflammation, immune suppression, and others, all of which seriously affect the patient’s quality of life [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the cause of prostate cancer is not yet fully understood, many studies have suggested that several risk factors are associated with the development of prostate cancer, including environmental factors, family history, age, and lifestyle [5,6]. At present, various treatments are accessible for patients with PCa using Western medicine, including radical prostatectomy (RP, removal of the prostate), radiotherapy (use of high-energy X-rays to kill cancer cells), chemotherapy (use of chemicals to kill cancer cells), androgen deprivation therapy, and immune therapy [7,8,9,10,11,12,13]. However, these therapies are costly and often cause a series of adverse side effects, such as decreased libido, erectile dysfunction, hot flashes, night sweats, castration syndrome, including such symptoms as anemia, metabolic abnormalities, and radioactive inflammation, immune suppression, and others, all of which seriously affect the patient’s quality of life [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We applied the methods in Table 1 to claims data of patients with mCRPC, which was obtained from a large national private health insurance network (Optum Clinformatic Data Mart). Our data consisted of a subset of a previously identified cohort, [59][60][61] which included patients who had at least one diagnosis of prostate cancer from January 1, 2010 to September 30, 2016 and used at least one of the six focus drugs (docetaxel, abiraterone, enzalutamide, sipuleucel-T, cabazitaxel, and radium-233) after the diagnosis. Since radium-233 were approved by FDA and released to the market later than the other five drugs, we restricted our cohort to patients who initiated treatment after January 1, 2014 to give them a fair comparison and make the results more generalizable to the current mCRPC population.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…In fact, the difference in OS was only 2.8 months between sipuleucel-T arm and placebo arm in patients in the highest quartile of PSA; conversely, according to this analysis, a survival benefit of 13 months was detected in the lowest quartile of PSA. Sipuleucel-T has been the first cellular therapeutic vaccine approved by the FDA, thus representing an historical step for cancer vaccines in medical oncology; nonetheless, more recent trials tempered the enthusiasm for this agent and, as suggested by a large real-world study conducted by Caram and colleagues on 7272 mCRPC patients, only one out of 10 cases were treated with sipuleucel-T, indicating the overall limited use of this cancer vaccine in everyday clinical practice [ 78 , 79 , 80 ].…”
Section: Prostate Cancer Vaccinesmentioning
confidence: 99%